(untitled) (Quinto Sol, 2020)
The institutions with international vocation are an excellent entry to study the conformation of the South American social reality, in a context of development of Pan-Americanism and of the agencies of the League of Nations. The Argentine Social Museum, inaugurated in 1911, was born as an answer to think about the social issue from a national perspective, but without losing sight of its international dimension. This article analyzes the links that the MSA established with the Paris Social Museum, the Carnegie Endowment and the social reformers in the Southern Cone of America. It is worth noting the ideological framework of its foundation and the values it promoted, as well as the connections with European intellectuals and the American continent.